2016
DOI: 10.3390/ijerph13111073
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Air Temperature on Accidental Casualties in Beijing, China

Abstract: Emergency room (ER) visits for accidental casualties, according to the International Classification of Deceases 10th Revision Chapters 19 and 20, include injury, poisoning, and external causes (IPEC). Annual distribution of 187,008 ER visits that took place between 2009 and 2011 in Beijing, China displayed regularity rather than random characteristics. The annual cycle from the Fourier series fitting of the number of ER visits was found to explain 63.2% of its total variance. In this study, the possible effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…Generally, most previous studies suggested a significant association between high temperature and falls (Parslow et al, 2005;Adam-Poupart et al, 2015) or RTIs (Nofal and Saeed, 1997;Basagaña et al, 2015). Similar to the findings of our study, a study in Beijing (China) (Ma et al, 2016) found that accidental casualties happen more frequently on warm days, and the greatest possibility of emergency visits for accidental casualties occurred at 26 °C. An Italian study assessing the relationship between workrelated accidents and hot weather conditions reported that the peak of accidents occurred on days with high but not extreme temperatures (24.8-27.5 °C) (Morabito et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, most previous studies suggested a significant association between high temperature and falls (Parslow et al, 2005;Adam-Poupart et al, 2015) or RTIs (Nofal and Saeed, 1997;Basagaña et al, 2015). Similar to the findings of our study, a study in Beijing (China) (Ma et al, 2016) found that accidental casualties happen more frequently on warm days, and the greatest possibility of emergency visits for accidental casualties occurred at 26 °C. An Italian study assessing the relationship between workrelated accidents and hot weather conditions reported that the peak of accidents occurred on days with high but not extreme temperatures (24.8-27.5 °C) (Morabito et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…We speculate that ambient temperature may affect outdoor behavioral patterns in children and adolescents and traffic intensity (Liang et al, 2021). In our study, moderate temperatures may promote the outdoor physical activity among children and adolescents and increase traffic intensity (Cools et al, 2010), which eventually increases the risk of outdoor falls and RTIs (Morabito et al, 2006;Morency et al, 2012;Ma et al, 2016). Our findings suggest that safety education and injury protection measures for outdoor activities must be further strengthened in children and adolescents when ambient temperature is supportive of outdoor activities.…”
Section: Discussionmentioning
confidence: 59%
“…In winter, sunlight travels longer through the atmosphere where the UVB is absorbed to a greater degree. Moreover, because the average temperature in Beijing during winter months (December, January, and February) is typically below 0 °C [13], people usually dress much thicker and expose significantly less skin in winter than in other seasons. This can also lead to a significant birth season disparity in the infants' vitD level between autumn and winter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the effect of meteorological factors is time-dependent and is not linear in most cases (Gasparrini et al, 2012). Such lagged effect might be related to the indirect effect of meteorological factors on immunity and thermoregulatory capacity (Ma et al, 2016). At present, the short-term effects of ambient temperature on mortality have been found by many studies worldwide (Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 97%